Calculation of the distribution of river sediments by the depth of the stream - Arifjanov Aybek; Apakhodjaeva Tursunoy; Atakulov Dinislam; Tursunova Elza; Iminov Ilxomjon (BIO Web of Conferences)
This article presents an analysis of the calculation of the distribution of river flow in the irrigation system by depth of flow. These studies aim to understand the dynamics of river flows and the impact of irrigation, with researchers dedicating years to this endeavor . In the clarifiers, the larger and medium fractions of sediments should be retained in such quantities that they cannot be transported by the downstream channels. In this case, it is not allowed to re-cool the water in the clarifier, as this will cause the channels in the system to be washed and reduce the fine particles that will increase the productivity of the fields It is known that many scientific studies have been conducted on the depth of river flows. In this case, we will analyze the distribution of river sediments along the depth of the current, using the proposed formulas for calculation. Furthermore, research has demonstrated that the distribution of river flows by depth follows a linear pattern with increasing flow rate or a higher percentage of smaller fractions in suspended particle composition. This distribution characteristic has been observed in various related studies. The practical and scientific findings of these studies are exemplified through research conducted at the “Ekin-Tekin Pumping Station” in the Andijan region, serving as a significant case study in this field. We chose the “Ekin-Tekin pumping station„ located in the Andijan region, as the object of research, and calculated the distribution of turbidity of the river at this pumping station depending on the depth of the flow.